2011
DOI: 10.1016/s1473-3099(11)70060-3
|View full text |Cite
|
Sign up to set email alerts
|

Community-based intervention to increase HIV testing and case detection in people aged 16–32 years in Tanzania, Zimbabwe, and Thailand (NIMH Project Accept, HPTN 043): a randomised study

Abstract: SUMMARY BACKGROUND HIV counseling and testing is the gateway to treatment and care and provides important preventative and personal benefits to recipients. However, in developing countries the majority of HIV infected persons have not been tested for HIV. Combining community mobilization, mobile community-based HIV testing and counseling, and post-test support may increase HIV testing rates. METHODS We randomly assigned half of 10 rural communities in Tanzania, 8 in Zimbabwe, and 14 in Thailand to receive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
210
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(217 citation statements)
references
References 28 publications
(23 reference statements)
5
210
1
Order By: Relevance
“…The findings in Vivek are consistent with previous studies where an increase in HIV testing rate was observed in community based VCT program [19]. Despite the widespread availability of VCT tests through project-supported static clinics, uptake of HIV testing was low.…”
Section: Discussionsupporting
confidence: 89%
“…The findings in Vivek are consistent with previous studies where an increase in HIV testing rate was observed in community based VCT program [19]. Despite the widespread availability of VCT tests through project-supported static clinics, uptake of HIV testing was low.…”
Section: Discussionsupporting
confidence: 89%
“…42 Recent evidence suggests that community-based testing can identify individuals earlier in the course of HIV infection 43 and increases knowledge of HIV status fourfold relative to healthfacility-based testing. 44 Reductions in mortality, costs and the rate of new infections will also depend crucially on maintaining good links with personnel monitoring and caring for individuals before they receive ART, on maximizing the retention rate and on initiating ART as early as permitted by national guidelines. These actions will help achieve the Millennium Development Goals on HIV infection.…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…Alternative approaches, including community-based testing, with appropriate support services yields better dividends as has been seen in Tanzania, Zimbabwe and Thailand. 9 Our study is limited by the fact that we do not know if HIV prevalence among patients with TB in centres without HIV testing is different from that of patients with TB in centres with HIV testing. Although this could potentially influence the HIV-positive yield, it is unlikely to make a considerable difference since overall HIV prevalence in patients with TB is generally low.…”
Section: Discussionmentioning
confidence: 91%